Thomas Jefferson [videorecording (DVD)] - Burns, Ken, 1953-; Waterston, Sam; Davis, Ossie; Ward, Geoffrey C. (PBS Home Video, 2004)
Examines the life of Thomas Jefferson, third President of the United States and author of the Declaration of Independence.